Hubungan Tingkat Pengetahuan Dan Pendidikan Terhadap Kepatuhan Divaksinasi Covid-19 Pada Masyarakat Wilayah Kerja Puskesmas Rajabasa Indah Bandar Lampung - Trisna Nur Aqilla Fadia Haya; Khoidar Amirus; Dalfian Dalfian (Universitas Malahayati Lampung, 2022)
ABSTRACT Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The handling of COVID-19 that must be implemented is one of the COVID-19 vaccines. The purpose of vaccination is to reduce transmission, reduce morbidity, and mortality, achieve herd immunity in the community, and protect the community from COVID-19. However, based on the results of the survey, 7 (70%) of 10 (100%) people did not comply with the covid-19 vaccination. It is known the relationship between the level of knowledge and education to compliance with covid-19 vaccination in the community of the Rajabasa Indah Health Center working area in 2021. Quantitative research uses observational analytical research with a cross-sectional approach. Sampling using accidental sampling technique as many as 214 respondents with questionnaires then analyzed using Chi-Square test. The distribution of knowledge and education from 214 respondents obtained the most knowledge from both 117 (54.7%) respondents, 112 higher education (52.3%) respondents, and the distribution of compliance obtained the most obedient vaccinated against COVID-19 among 132 (61.7%) respondents. From the results of The Chi-Square test analysis obtained p-value = 0.000 (p0.05), there is a significant relationship between the level of knowledge and education on compliance with covid-19 vaccination in the community of the Rajabasa Indah Puskesmas Bandar Lampung working area. It is recommended that the public be expected to increase knowledge about the symptoms of COVID-19, the age group that is susceptible to being affected, the handling of COVID-19 patients, the use of masks, and how to wash their hands. Keywords: Knowledge, Education, COVID-19, Vaccination COVID-19. ABSTRAK Coronavirus Disease 2019 (COVID-19) adalah penyakit menular yang disebabkan Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Penanganan COVID-19 yang harus dilaksanakan salah satunya vaksin COVID-19. Tujuan vaksinasi adalah mengurangi penularan, menurunkan angka kesakitan, kematian, mencapai kekebalan kelompok di masyarakat dan melindungi masyarakat dari COVID-19. Namun berdasarkan hasil presurvei didapatkan 7 (70%) dari 10 (100%) orang tidak patuh dilakukan vaksinasi COVID-19. Diketahui hubungan tingkat pengetahuan dan pendidikan terhadap kepatuhan divaksinasi COVID-19 pada masyarakat wilayah kerja Puskesmas Rajabasa Indah Tahun 2021. Penelitian kuantitatif menggunakan penelitian analitik observasional dengan pendekatan cross sectional. Pengambilan sampel menggunakan teknik accidental sampling sebanyak 214 responden dengan kuesioner selanjutnya dianalisis menggunakan uji Chi- Square. Didapatkan distribusi pengetahuan dan pendidikan dari 214 responden paling banyak pengetahuan baik 117 (54,7%) responden, pendidikan tinggi 112 (52,3%) responden, dan distribusi kepatuhan didapatkan terbanyak patuh divaksinasi COVID-19 132 (61,7%) responden. Dari hasil analisis uji Chi-Square diperoleh p value = 0,000 (p0,05), terdapat hubungan signifikan antara tingkat pengetahuan dan pendidikan terhadap kepatuhan divaksinasi COVID-19 pada masyarakat wilayah kerja Puskesmas Rajabasa Indah Bandar Lampung. Disarankan bagi masyarakat diharapkan menambah pengetahuan mengenai gejala COVID-19, kelompok usia yang rentan terkena, penanganan pasien COVID-19, penggunaan masker, serta cara mencuci tangan. Kata Kunci: Pengetahuan, Pendidikan, COVID-19, Vaksinasi COVID-19